2013
DOI: 10.1007/s12031-013-0110-9
|View full text |Cite
|
Sign up to set email alerts
|

Association of Imaging Classification of Intracranial Cerebral Atherosclerotic Vascular Stenosis in Ischemic Stroke and Renalase Gene Polymorphisms

Abstract: Cerebral atherosclerosis vascular stenosis is a common etiology for ischemic stroke and a major factor in recurrent stroke and vascular mortality. Recent studies suggest that renalase plays a role in hypertension and ischemic stroke, and may be involved in atherosclerosis. The aim of the present study was to investigate whether there were correlations between single-nucleotide polymorphisms (SNPs) in the renalase gene and severity of intracranial cerebral atherosclerotic vascular stenosis in ischemic stroke pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…Correlation between renalase SNPs and severity of intracranial cerebral atherosclerotic vascular stenosis was examined in 212 ischemic stroke patients and 244 healthy controls from the northern Chinese Han population [25]. SNP rs10887800 in the renalase gene was associated with severe intracranial cerebral atherosclerotic vascular stenosis.…”
Section: Disease Association With Renalase Single Nucleotide Polymorpmentioning
confidence: 99%
“…Correlation between renalase SNPs and severity of intracranial cerebral atherosclerotic vascular stenosis was examined in 212 ischemic stroke patients and 244 healthy controls from the northern Chinese Han population [25]. SNP rs10887800 in the renalase gene was associated with severe intracranial cerebral atherosclerotic vascular stenosis.…”
Section: Disease Association With Renalase Single Nucleotide Polymorpmentioning
confidence: 99%
“…Intracranial atherosclerosis can be considered as a multifactorial process in which atherosclerotic risk factors like hypertension, dyslipidemia, diabetes, were involved in the disease development process [29][30][31][32]. Hereditary factors are also believed to play important roles in sICAS as associations of intracranial atherosclerosis and genetic polymorphisms are described in several studies [8][9][10][11][12][13][14][15]. Thus, 96 SNPs were examined in the present study, which were all proved to be related to ischemic stroke, atherosclerosis and coronary atherosclerotic heart diseases.…”
Section: Discussionmentioning
confidence: 89%
“…Yet, unlike other vascular diseases, little is known regarding associations of sICAS and genetic polymorphisms. Recent genetic studies have suggested the importance of genetic factors in predisposition to sICAS such as genotypes or polymorphisms of APOE, CRP, Renalase, RNF213, LPL and ALDH2 [8][9][10][11][12][13][14][15][16], but few candidate genes have been replicated. Genetic research of subjects who had sICAS can be a promising approach for identification of novel biological mechanisms that underlie the development of sICAS.…”
Section: Introductionmentioning
confidence: 99%
“…Our results demonstrate the top level genes that are related to normal vascular physiology, viz. genes of nitric oxide synthesis, endothelial health and smooth muscle biology .…”
Section: Discussionmentioning
confidence: 99%
“…We found renalase has comparative high relationship with IS; this gene encodes a novel flavin adenine dinucleotide‐dependent amine oxidase . This enzyme is secreted by the kidney and functions to catabolize circulating catecholamines, thus having a direct effect on cardiac function and systemic blood pressure (BP).…”
Section: Discussionmentioning
confidence: 99%